The negative effect of the chicken feather meal in the diet on growth performance of the shortfin eel Anguilla bicolor larvae - Muhammad Y. Thamren; Agung Setia Batubara; Nurfadillah Nurfadillah; Irma Dewiyanti; Zainal A. Muchlisin (Syiah Kuala University, 2018)
The aim of these study was to examine the effect of the replacement fish meal with chicken feather meal (CFM) for eel Anguilla bicolor larvae. The study was conducted at the Laboratory of Ichthyology, Faculty of Marine and Fisheries of Syiah Kuala University on September to October 2017. The Complete Randomized Design (CRD) with 7 treatments and 4 replications were used in this study. The tested dosage of CFM were of 0% CFM (control), 10% CFM, 20% CFM, 30% CFM, 40% CFM, 50% CFM and 60% CFM, where each treatment were contained of protein 32.26% (0% CFM), 33.09% (10% CFM), 36.20% (20% CFM), 39.10% (30% CFM), 41.22% (40% CFM), 45.43 ( 50% CFM) and 40.02% (60% CFM). The experimental fish were stocked in the plastic container at the stocking density of 15 fish container-1 and fed the experimental diets at the feeding level of 10% body weight a day for 60 days. The results showed that the application of CFM in the diet was not given a significant effect on the weight gain, daily weight gain, specific growth rate (P0.05). In addition, the fish fed on CFM did not show growth rate even reduces the body weight of the experimental fish. It is concluded that the application of the CFM in diet gave the negative effect on the growth performance of the eel larvae.